Plio-Pleistocene Neodymium (Nd) isotope data for Ocean Drilling Program (ODP) Site 967, Eastern Mediterranean - Udara Amarathunga; Eelco J Rohling; Katharine M Grant; Alexander Francke; James Latimer; Robert M Klaebe; David Heslop; Andrew Roberts; David K Hutchinson (PANGAEA, 2024)
Past North African humid periods resulted in expanded vegetation over the Sahara, due to northward tropical African rainbelt displacement. Commonly, these precession-timed North African humid periods ended within 15 thousand years as the monsoon rainbelt retreated southward during subsequent dry intervals. Eastern Mediterranean organic-rich layers (sapropels) reflect North African humid periods through out the Plio-Pleistocene, which are interbedded with the marls deposited during intervening dry periods. ODP Site 160-967 in the eastern Mediterranean is composed of sediments delivered from North Africa back to the Miocene/Pliocene boundary. Here we present a low-resolution Neodymium isotope record for the past 5 million years (from sapropels and marls), which reflects sediment source region variability to the eastern Mediterranean across the Plio-Pleistocene.